1989
DOI: 10.1128/aac.33.8.1160
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of CP-65,207, a new penem antimicrobial agent, in comparison with those of other agents

Abstract: CP-65,207 is a new parenteral penem antibiotic with a broad spectrum that includes gram-positive, gram-negative, and anaerobic microorganisms, with MICs for 90% (MIC90s) of the majority of 1,101 clinical pathogens tested being '1 ,ig/ml. The compound was from 10-to 100-fold more active than cefoxitin and broad-spectrum cephalosporins against gram-positive bacteria and anaerobes. CP-65,207 was less active than imipenem for staphylococci, group A streptococci, and Enterococcus faecalis. Against members of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Gootz and coworkers (13) in their 1989 study on CP-65,207, reported on its activity against 84 anaerobes, many of which have since been reclassified. Excluding Peptococcus spp., which are no longer included among clinically significant anaerobic gram-positive cocci in standard manuals (16), their results were similar to those obtained in our study.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gootz and coworkers (13) in their 1989 study on CP-65,207, reported on its activity against 84 anaerobes, many of which have since been reclassified. Excluding Peptococcus spp., which are no longer included among clinically significant anaerobic gram-positive cocci in standard manuals (16), their results were similar to those obtained in our study.…”
mentioning
confidence: 99%
“…CP-65,207, whose in vitro activity was published in 1989 (13), is a diastereomeric mixture of two isomers, the active component of the two being sulopenem. Sulopenem development was put on hold in the 1990s as discovery/development efforts were focused on gram-positive organisms.…”
mentioning
confidence: 99%
“…MexXY-OprM and MexCD-OprJ extrude most penicillins but not carbenicillin, sulbenicillin, various cephems, and many carbapenems. Penem antibiotics display potent activities against a variety of gram-positive and gram-negative bacteria but not against P. aeruginosa (2,3,4,13,15,16,17,21,24). Studies with mutants that overproduce or lack MexAB-OprM demonstrated that this efflux system extrudes penem antibiotics (18).…”
mentioning
confidence: 99%
“…infusions of 1 g of CP-65,207-S produce concentrations in serum in excess of 1.0 jig/ml, the MIC for 90% of over 1,000 hospital pathogens (8), for approximately 3.5 h. Since CP-65,207 (and presumably the single isomers) produce very rapid killing of bacteria (8), the results suggest that 1-g doses of CP-65,207-S may be effective against many infections. The oral prodrug CP-65,207-POM produces appreciable concentrations of both isomers of CP-65,207 in serum.…”
Section: Resultsmentioning
confidence: 99%
“…CP-65,207 (2) is a potent broad-spectrum antibacterial agent with activity comparable to that of imipenem, with the exception that it has significantly lower activity against Pseudomonas aeruginosa (8). The MIC for 90% of over 1,000 hospital pathogens was approximately 1.0 jig/ml (8).…”
mentioning
confidence: 99%